Audiovisual telesupport system for cardiovascular catheter interventions: A preliminary report on the clinical implications. Issue 5 (31st July 2019) - Adachi, Toru; Sato, Akira; Kuroki, Kenji; Terai, Tomoko; Hanaoka, Daisuke; Hiraya, Daigo; Machino, Takeshi; Nogami, Akihiko; Ieda, Masaki; Aonuma, Kazutaka
Abstract: Objectives: This study aimed to validate the clinical implications of audiovisual telesupport system use. Background: An audiovisual telesupport system with supervisors has been effective in guiding procedures when surgeons have limited experience with the technique. However, cardiovascular catheter interventions using an audiovisual telesupport system has not been previously reported. Methods: Starting in September 2017, two cardiologists in Kamisu Saiseikai Hospital (Kamisu, Japan, with limited cardiologists) began performing cardiovascular catheter interventions using an audiovisual telesupport system. This system enabled them to perform catheter interventions with the support of advisors in the University of Tsukuba (Tsukuba, Japan). We retrospectively assessed procedure time and complications of percutaneous coronary intervention (PCI) and catheter ablation (CA). Results: In the first 10 months, 21 patients with coronary artery disease underwent PCI using this system. The mean procedure duration of PCI was 42 ± 10 min. Nine patients with tachyarrhythmia including supraventricular tachycardia (SVT), ventricular premature contraction (VPC), common atrial flutter, and paroxysmal atrial fibrillation (AF) underwent CA using this system. The mean CA procedure time was 134 ± 31 min for SVT, 100 ± 14 min for VPC, and 200 min for AF. All PCI and CA procedures were successfully performed without any complications. Conclusions: The audiovisual telesupport system enabled cardiologists with limited human resources to provide safe and high‐quality catheter interventions.